Local names Aceraceae, Hamamelidaceae, Leguminosae, Fabales, Betulaceae, Ebenaceae, Fagaceae, Buxaceae, Juglandaceae trees in Iran - Ghassem Habibi Bibalani; Prisa Mohamadpour; Fatemeh Mosazadeh SayadMahaleh (بیولوژی کاربردی, 2020)
Objectives: Social linguistics is a type of linguistic study that is known as a cultural subject that is closely related to the social relations of the community that speaks that language. The purpose of this study is to identify and record the different names used for trees, shrubs and shrubs in different regions of Gilan, Mazandaran and Golestan provinces from Astara to Ramyan. These provinces also had local names registered. Materials and Methods: The present research has been done by field method and library study. Although all the researchers in this study are fully acquainted with the Gilaki language and dialect, however, to determine the exact Persian equivalent of words and tree-related entries in different local dialects, interview speakers of this language (especially people over 60 years of age Year) did. All the words and terms of this research are related to the most important words and terms related to the trees, shrubs and bushes of the families of the tribes of Aceraceae, Hamamelidaceae, Leguminosae, Fabales, Betulaceae, Ebenaceae, Fagaceae, Buxaceae, Juglandaceae in different regions of Gilan, Mazandaran and Golestan. Results: In this study, 102 local names for the trees of the genus Aceraceae (23 local names), Hamamelidaceae (2 local names), Leguminosae (14 local names), Fabales(18 local names), Betulaceae (9 local names), Fagaceae (20 Local names), Buxaceae (6 local names) and Juglandaceae (10 local names) in Iran, which are mainly the names used in the three provinces of Gilan, Mazandaran and Golestan in different dialects, were recorded. Based on the results of this research, Acer laetum with local names of Bezberg (in Gorgan), Mirzaberg (in Ramyan), Pellet (in Gilan), Milky (in Noor, Kojoor and Mazandaran) and Zbandar (in Bandar-e-Gaz); Acer opulifolium with the local names of Cerco (in Ramyan) and Sefid Cerco (in Katul); Acer platanoides with the local letters Kirk (in pilgrimage) and Kakum (in its length); Alnus glotinosa with the local names of Siatuse (in Lahijan), Tosa (in Rudsar), Tose (in Rasht), Alder (in Gorgan and Mazandaran) and Yellow (in Astara and Tavalesh) are called.